VD_FINDINFO 32/2011 vom 21. Dezember 2011 - VD Tribunal cantonal (2011)
RÉCUSATION, EXPERT | 6 par. 1 CEDH, 42 CPC, 29 Cst., 30 al. 1 Cst., 183 al. 2 CPC (CH), 320 CPC (CH), 50 al. 2 CPC (CH), 51 al. 1 CPC (CH), 8a al. 7 CDPJ